Poetics, politics and protest in Arab theatre : the bitter cup and the holy rain - Ḥamdān, Masʻūd (Sussex Academic Press, 2006)
Writing from a socio-historical point of view, the author surveys and discusses the popular theatrical phenomena in the Arab world from the Hellenic period to the beginning of the 21st century. He notes the Eastern carnivalesque folk sources and the tendency toward comedy rather than tragedy.